2020
DOI: 10.1162/jocn_a_01497
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Role for Top–Down Modulation from Frontal Cortex in Infancy

Abstract: Recent findings have shown that full-term infants engage in top–down sensory prediction, and these predictions are impaired as a result of premature birth. Here, we use an associative learning model to uncover the neuroanatomical origins and computational nature of this top–down signal. Infants were exposed to a probabilistic audiovisual association. We find that both groups (full term, preterm) have a comparable stimulus-related response in sensory and frontal lobes and track prediction error in their frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…As such, anticipatory alpha may be a promising, developmentally consistent neural correlate for measuring the binding of prediction and action (Brown et al, 2011;Feldman & Friston, 2010), useful for testing computational, action-oriented cognitive neuroscience (Engel et al, 2013;Friston et al, 2011;Huang & Rao, 2011). This study advances an integrative perspective of anticipation while also narrowing down an instance in time and activity in which prediction is evident (Baek et al, 2020;Jaffe-Dax et al, 2020), with potential for considering how individual differences in behavior and cognitive abilities reflect the accumulation of multilevel, multimodal developmental processes (Marshall, 2014).…”
Section: Future Directions: Anticipation As a Malleable Indicator Of ...mentioning
confidence: 98%
“…As such, anticipatory alpha may be a promising, developmentally consistent neural correlate for measuring the binding of prediction and action (Brown et al, 2011;Feldman & Friston, 2010), useful for testing computational, action-oriented cognitive neuroscience (Engel et al, 2013;Friston et al, 2011;Huang & Rao, 2011). This study advances an integrative perspective of anticipation while also narrowing down an instance in time and activity in which prediction is evident (Baek et al, 2020;Jaffe-Dax et al, 2020), with potential for considering how individual differences in behavior and cognitive abilities reflect the accumulation of multilevel, multimodal developmental processes (Marshall, 2014).…”
Section: Future Directions: Anticipation As a Malleable Indicator Of ...mentioning
confidence: 98%
“…The authors found that while the neural and behavioral signatures of audiovisual learning were intact, infants did not show neural signatures of sensory prediction (also see Refs. 58 and 59 ).…”
Section: Individual Variation: Uncovering Different Developmental Tra...mentioning
confidence: 99%
“…This is a pressing issue as it has been established that infants have more sophisticated cognitive and learning abilities than previously believed. For example, neuroimaging work has established that infants are employing higher-level neural systems (e.g., the prefrontal cortex) in a variety of tasks (Grossmann, 2013;Jaffe-Dax et al, 2019;Werchan & Amso, 2017;Werchan et al, 2016). These learning abilities enabled infants to form rich representations of the external world, which could be a source of top-down signals.…”
Section: Introductionmentioning
confidence: 99%
“…As infants' top-down processes were restricted to neuroimaging findings, what remains unknown is whether these neural signatures of topdown modulation were behaviorally meaningful. Establishing behavioral signatures of top-down perceptual modulation is crucial for numerous reasons: 1) Prominent critiques of top-down processes have argued that neuroimaging evidence cannot be considered evidence of top-down perception (Firestone & Scholl, 2016); 2) These neuroimaging findings could have a variety of cognitive consequences from modifying perception to supporting learning through communicating error signals to other brain regions (e.g., Jaffe-Dax et al, 2019); and 3) Neural changes can happen below a threshold for behavioral changes. This was particularly the case when considering early competencies in immature brains (Karuza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%